Jennifer Egan, Hibriditas Sastra, dan Perkembangan Avant Garde di Amerika; Kajian Sosiologis Terhadap Novel A Visit From The Goon Squad - Ali Imron (Universitas Tidar, 2016)
This paper focuses on analyzing a novel entitled “A Visit from the Goon Squad” using sociological approach. The purpose is to reveal the connection between the content of the novel with the social background and history when it was written and also with the social background and biography of the author. The connection is to reveal the improvement of a literary movement in America at the time. The result shows that the author uses an experimental combination in writing the novel which is much more influenced by the use of computer. Many contents of the novel are in form of table, graphic, and some other types of presentation which are not considered as part of literary work form. This kind of style applied is largely considered as a hibridity in literature and is under the avant garde movement.Key words: Jennifer Egan, sociologcal approach, hibridity, avant garde movement in America.